Dosimetric Assessment of Routine X-Ray Examination at Selected Health Clinics in Perak Using Commercialized Optically-Stimulated Luminescence Dosimeter (OSLD) - M. T. Saidin; A. A. Rahman; H. H. Harun; Y. M. Radzi; C. Anam; Z. Kayun (Atom Indonesia, 2021)
This study aims to compare entrance surface dose (ESD) values measured with nanoDot Al2O3:C optically-stimulated luminescence dosimeter (OSLD) and guidance level set under the second national dose survey which utilized old-version LiF:Mg,Ti thermoluminescence dosimeter (TLD). In this study, we conducted a dosimetric assessment for posteroanterior chest X-ray (PA-CXR) examinations performed at various community clinics in Perak, Malaysia. These clinics were selected as they were excluded from the first and second national dose survey conducted in Malaysia in 1993-1995 and 2005-2009, respectively. The ESD is obtained by mounting the OSLD on the surface of polymethyl methacrylate (PMMA) slabs. The PMMA slabs were then exposed to X-ray based on the current practice of respective clinics. The results show that the 3rd quartile of ESDs ranged from 0.180 mGy to 0.229 mGy which is less than the recommended guidance level of the second national dose survey by 77 %. ESD measured using OSLD was found to be lower than the guidance values recommended from the second national dose survey. The finding showed a good competency of the radiographer to optimize radiological practice specifically in routine X-ray examination.